2019
DOI: 10.18689/mjn-1000129
|View full text |Cite
|
Sign up to set email alerts
|

Nursesʼ Perceptions of Incivility in the Operating Room

Abstract: The operating room (OR) can be a high-stress area for healthcare workers. A great deal of expertise, teamwork, and precision is needed for the area to run smoothly and achieve desired patient outcomes. Incivility in healthcare has been recognized in the literature as a cause of healthcare worker distraction with increased risk of medical errors, reduce collegiality, and employee turnover. A survey was sent to nurses who work in operating rooms in a southern state. Forty-three nurses responded to the survey. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The results also showed that nurse manager ability, leadership, support of nurses, and staffing and resource adequacy are potential avenues to address coworker incivility. The result of this study coincides with the study by Garth et al (2019) in that nursing leadership plays a critical role in shaping the nurse work environment that ultimately drives better nurse outcomes with the elimination of workplace incivility. A respectful, civil work environment should be a priority for every hospital administrator in order to allow nurses to focus on providing exceptional patient care (Smith et al, 2018).…”
Section: Methodological Approachessupporting
confidence: 86%
See 3 more Smart Citations
“…The results also showed that nurse manager ability, leadership, support of nurses, and staffing and resource adequacy are potential avenues to address coworker incivility. The result of this study coincides with the study by Garth et al (2019) in that nursing leadership plays a critical role in shaping the nurse work environment that ultimately drives better nurse outcomes with the elimination of workplace incivility. A respectful, civil work environment should be a priority for every hospital administrator in order to allow nurses to focus on providing exceptional patient care (Smith et al, 2018).…”
Section: Methodological Approachessupporting
confidence: 86%
“…Fifty-six percent ( n = 22) have dreaded going to work due to uncivil behavior in the operating room. Similar to the findings of Hamlin et al (2016), Garth et al (2019) found that uncivil behaviors were reported most commonly as being committed by operating room physicians and nurse colleagues. The most common reported uncivil behavior by fellow operating room nurses was gossiping about other nurses, with 83.79% ( n = 31).…”
Section: Methodological Approachessupporting
confidence: 86%
See 2 more Smart Citations
“…In their study, Rosenstein and O'Daniel 2005 had noticed that 86% of nurses had encountered these behaviors, and physicians had additionally expressed that in half of their fellow workers had witnessed such behaviors. [12] Besides, Garth et al 2019 had reported that the prevalence rate of unpleasant and uncivil behaviors with nurses by physicians was approximately 66% [13].…”
Section: Operating Rooms Problem Behavior Operating Room Nursing Cmentioning
confidence: 99%